Fisioterapi dengan Metode Senam Hamil Untuk Mengurangi Nyeri Punggung Bawah Pada Ibu Hamil Trimester III - Renni Hidayati Zein; Gita Dwiyani (LPPM Universitas Abdurrab, 2022)
Bacground: Pregnancy is a process that occurs between the fusion of sperm and ovum so that conception occurs until the birth of the fetus, the length of a normal pregnancy is 280 days or 40 weeks calculated from the first period of the last menstrual period (LMP). Low back pain (lumbago) is back pain that occurs in the lumbosacral area. Low back pain is discomfort that occurs below ribs and above the inferior gluteal area. Pregnancy exercise is a form of exercise that aims to strengthen the abdominal and flex the joints. Pregnancy exercise plays a role in strengthening contractions and maintaining the strength of the abdominal wall muscles, ligaments, pelvic floor muscles and others that withstand additional pressure to reduce low back pain. Purpose: To determine the effectiveness of pregnancy exercise to reduce back pain below in third trimester pregnant women. Research Method : case study presented in the form of descriptive narrative. The research subject consisted of 1 sample that met the sample criteria. The study was conducted for 12 times of therapy which was carried out on 13-12 May 2022 at the Rosita Midwife Clinic Pekanbaru. Evaluation using Numerical Rating Scale (NRS). Result: : This study showed that there was a decrease in pain from before the intervention with a silent pain value of 7, tenderness 5 and motion pain 7 until the 12th therapy obtained a silent pain value of 5, tenderness 2 and motion pain 4.Keywords: Pregnancy exercise, LBP.